A self-healing modified binder for lithium battery silicon negative electrode and its preparation method and application

By using self-healing modified binder in the silicon anode of lithium-ion batteries, problems such as circulation stability, volume expansion and initial Coulomb efficiency of traditional silicon anode materials are solved, and higher peel strength and self-healing ability are achieved, improving the overall performance of the battery.

CN119391332BActive Publication Date: 2025-04-01JIANGSU YITE NEW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510000289.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-01
Estimated Expiration
2045-01-02

AI Technical Summary

Technical Problem

The silicon negative electrode materials in traditional lithium-ion batteries have problems in cycle stability, volume expansion, initial Coulomb efficiency and processing costs, which hinder their commercial applications.

Method used

Using a self-healing modified binder, the preparation raw materials include polyacrylic acid, tannin acid and modified nanosilica composite materials, and the polymer cross-linked network structure is formed through mechanical dispersion to improve the peel strength and self-healing ability of the binder.

Benefits of technology

The peel strength and self-healing ability of the silicon negative electrode material are improved, the circulation and mechanical properties of the battery are improved, and the overall performance of the battery is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention provides a self-healing modified binder for lithium battery silicon negative electrode and its preparation method and application, wherein the self-healing modified binder comprises at least tannic acid, polyacrylic acid and modified nano-silicon dioxide composite material. The self-healing modified binder has abundant dynamic hydrogen bonds between molecules, and combined with the modified nano-silicon dioxide composite material incorporated, the self-healing modified binder is improved in hydrophobicity while also endowed with excellent self-healing performance, so that it can quickly restore its integrity when mechanically damaged, thereby effectively solving the problem of poor battery performance caused by volume expansion of silicon negative electrode during charging and discharging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium batteries, and in particular relates to a self-healing modified adhesive for a lithium battery silicon negative electrode, and a preparation method and application thereof. Background Art

[0002] Lithium ion batteries (LIBs) are an excellent energy storage system with high energy density and wide application due to the small size of lithium ions, which can easily move in the electrolyte between the positive and negative electrodes, thus providing high voltage, charge storage per unit volume (700Wh / L) and unit mass (260Wh / kg). In addition to powering a range of portable electronic devices such as laptops and mobile phones, lithium-ion batteries have revolutionized the way electric bicycles and hybrid electric vehicles are powered. However, the performance of traditional LIBs is still limited and cannot meet the requirements of large-scale vehicle electrification. In order to achieve the goal of all-electric vehicles powered by lithium-ion batteries for long-distance travel (>500km), it is urgent to develop next-generation lithium-ion batteries with higher energy density (>350Wh / kg). Therefore, researchers have been looking for new negative electrode materials, such as silicon (Si), which can produce high capacity to replace traditional graphite negative electrodes. Silicon has various properties that are superior to graphite and other candidate materials such as tin and germanium, including high theoretical capacity (4200 mAh / g), low operating voltage (~0.4 V vs. Li / Li+), abundant resources (28.2% in the earth's crust), and non-hazardous properties.

[0003] However, there are still several major obstacles in the development of Si anode. First, the poor cycle stability of Si anode and the large volume expansion (~400%) during charge and discharge cycles have not been completely solved. The significant volume expansion of Si anode after lithium insertion leads to the rupture and pulverization of Si particles and electrode stratification, which has a significant impact on battery performance. Second, the initial Coulomb efficiency is low. The Si anode will form a solid electrolyte interface film (SEI) during the first de-lithiation process, but under the influence of the volume change of silicon, the generated SEI film will be repeatedly destroyed and re-formed. Therefore, a large amount of lithium ions are consumed, resulting in a significant attenuation of electrochemical performance. In addition, the easy formation of an oxide layer on the silicon surface will trigger an irreversible reaction, resulting in a decrease in the initial Coulomb efficiency. Third, the cost of nano-sizing silicon materials is very high. When the size of silicon is reduced to the nanoscale, the processing cost will at least double. These problems have seriously hindered the commercial application of silicon-based anodes in lithium-ion batteries. Therefore, how to reduce the volume expansion of silicon particles during alloying / de-alloying is the mainstream bottleneck problem of silicon-based materials at present.

[0004] At present, the effective method to solve the problem of silicon negative electrode materials is to develop new binders. As a bridge between the current collector and the active material, the binder not only supports the structural integrity of the electrode, but also supports the continuous conductive path inside the motor. Therefore, compared with the preparation of modified silicon nanomaterials, low-cost, environmentally friendly, high-performance binders can promote the practical application and commercialization of silicon negative electrodes.

[0005] The existing silicon negative electrode binders mainly include PVA (polypropylene alcohol) binders and PAA (acrylic) binders. Due to the lithium transfer characteristics of PAA and PVA, lithium ions can jump between adjacent carboxyl and hydroxyl groups, thus forming a more or less thin coating on the surface of silicon particles, playing the role of artificial SEI to transfer ions. Among them, PVA binders only have hydroxyl groups but no carboxyl groups, and their ion transfer properties are poor. PAA binders, however, have a large number of carboxyl groups, which makes them very easy to absorb water, and produce too many hydrogen bonds between carboxyl groups, hindering the free rotation of the molecular chain, making the polymer too flexible, which is not conducive to bearing the stress generated by the volume expansion of the active material, affecting the improvement of battery performance, and the linear long chain structure of PAA makes it easy for the molecular chains to slide, and it is easy to cause permanent deformation after being stressed, resulting in the agglomeration of the active material, reducing the specific capacity of the electrode. Summary of the invention

[0006] In order to solve some of the problems in the prior art, the present invention provides a self-healing modified binder for lithium battery silicon negative electrode and a preparation method and application thereof.

[0007] A self-healing modified binder for lithium battery silicon negative electrode, wherein the raw materials for preparation include at least 100-150 parts of polyacrylic acid, 8-25 parts of tannic acid and 10-15 parts of modified nano-silicon dioxide composite material; wherein the modified nano-silicon dioxide composite material is prepared by copolymerization of borate monomer and methyl methacrylate on the surface of nano-silicon dioxide.

[0008] In some embodiments of the present invention, the method for preparing the modified nano-silicon dioxide composite material comprises the following steps:

[0009] S1: Preparation of borate monomer: N,N-dihydroxyethyl alkylamine, triethyl borate and solvent are placed in a reaction vessel equipped with an oil-water separator and a vacuum pressure reducing device, the water bath is controlled at 60-70°C, the vacuum degree is controlled at 0.02-0.04MPa, the reaction is carried out under reduced pressure and refluxed, and the reaction is stirred for 1-2h; N-hydroxymethyl acrylamide and a polymerization inhibitor are added, the reaction is continued for 1.5-2h, and unreacted raw materials and solvent are removed by reduced pressure distillation to obtain a borate monomer;

[0010] S2: Add protective colloid, emulsifier and deionized water into another reaction container, stir for 3-5 minutes, then add nano-silicon dioxide slurry, stir under ultrasonic wave, heat to 70-90°C, add methyl methacrylate and initiator, and react for 4-5 hours;

[0011] S3: Add borate monomer to the reaction system obtained in S2, then add initiator, heat to 80-90°C, react for 10-12h, add demulsifier, demulsify, filter, wash, and vacuum dry to obtain the modified nano-silica composite material.

[0012] In some embodiments of the present invention, the N,N-dihydroxyethylalkylamine in S1 is at least one of N-butyldiethanolamine, N-heptyldiethanolamine, 2,2'-(octylimino)diethanol, 2,2'-(cyclohexylimino)diethanol, p-ethyldihydroxyethylcyclohexylamine (CAS: 415948-31-1), and N,N-dihydroxyethyldodecylamine.

[0013] In some embodiments of the present invention, the molar ratio of the N,N-dihydroxyethylalkylamine to triethyl borate and N-hydroxymethyl acrylamide in S1 is 1-1.05:1:1-1.2.

[0014] In some embodiments of the present invention, the solvent in S1 is at least one of benzene, toluene, pentane, hexane, ether and acetone.

[0015] In some embodiments of the present invention, the oil-water separator in S1 is filled with at least one of magnesium chloride, calcium chloride, zinc chloride and copper sulfate for absorbing the produced ethanol.

[0016] In some embodiments of the present invention, the initiator in S2 is at least one of persulfates and peroxides, and its usage is 1-2% of the mass of methyl methacrylate; the initiator in S3 is at least one of persulfates and peroxides, and its usage is 1-2% of the mass of borate monomer.

[0017] In some embodiments of the present invention, the nano-silica contained in the nano-silica slurry used in S2 satisfies the mass ratio of methyl methacrylate: borate monomer: nano-silica = 1-5: 3-7: 90-95 in the system.

[0018] The structure of the borate monomer used in the modified nano-silicon dioxide composite material of the present invention is shown in Formula I, wherein R represents one of butyl, heptyl, octyl, cyclohexyl, and ethylcyclohexyl:

[0019]

[0020] Formula I

[0021] The preparation method of the self-healing modified binder for lithium battery silicon negative electrode of the present invention comprises the following steps: dissolving tannic acid in deionized water to form a tannic acid aqueous solution, then mixing with polyacrylic acid and modified nano-silicon dioxide composite material, and mechanically dispersing until uniform, so as to obtain the self-healing modified binder for lithium battery silicon negative electrode.

[0022] The present invention also provides the use of the self-healing modified binder for lithium battery silicon negative electrode in the lithium battery silicon negative electrode.

[0023] Beneficial effects: Compared with the prior art, the present invention uses polyacrylic acid as the binder system, adds tannic acid thereto, and utilizes the polar structures such as phenolic hydroxyl and carbonyl of tannic acid to interact with polyacrylic acid to form hydrogen bonds, thereby forming a polymer cross-linked network structure as a "dynamic binder", thereby improving the peel strength of the binder on the negative electrode material.

[0024] More importantly, the modified nano-silica composite material incorporated into polyacrylic acid is coated with a borate structure and a methyl methacrylate structure on the surface: a nitrogen atom is introduced into the borate structure to form an intramolecular BN coordination bond, which weakens the ability of the boron atom to accept external electron pairs and greatly improves the hydrolysis resistance of the borate; an oleophilic and hydrophobic monolayer is formed on the surface of the modified nano-silica, which can reduce the water absorption of polyacrylic acid when participating in the formation of a negative electrode binder; a three-dimensional network structure formed by the interweaving of tannic acid, polyacrylic acid and the surface of modified nano-silica not only gives the modified binder self-healing ability, but also improves the toughness of polyacrylic acid and improves the mechanical properties of the binder. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0026] The following is an exemplary description of the preparation process of the modified nano-silicon dioxide composite material used in the examples.

[0027] Modified Nano-Silica Composite Material #1

[0028] S1: Preparation of borate monomer: 16.1 g (0.1 mol) of N-butyldiethanolamine, 14.6 g (0.1 mol) of triethyl borate and 200 ml of solvent benzene were placed in a reaction vessel equipped with an oil-water separator (containing 10 g of magnesium chloride) and a vacuum pressure reducing device, the water bath was controlled at 60°C, the vacuum degree was controlled at 0.04 MPa, the mixture was refluxed under reduced pressure, and the reaction was stirred for 2 h; 10.1 g (0.1 mol) of N-hydroxymethyl acrylamide and 0.01 g of inhibitor phenothiazine were added, the reaction was continued for 2 h, and the unreacted raw materials and solvent were removed by vacuum distillation to obtain a borate monomer;

[0029] S2: Add 10g protective colloid polyvinyl alcohol, 10g emulsifier Tween T-20, and 100ml deionized water into another reaction container, stir for 3min, then add 90g nano-silica, stir under ultrasonication, heat to 70°C, add 3g methyl methacrylate and 0.03g initiator ammonium persulfate, and react for 4h;

[0030] S3: 7 g of borate monomer was added dropwise to the reaction system obtained in S2, and then 0.07 g of initiator ammonium persulfate was added thereto, the temperature was raised to 80°C, and after reacting for 12 hours, a demulsifier - a 5% by mass aluminum sulfate aqueous solution was added, the demulsifier was demulsified, filtered, washed, and vacuum dried to obtain the modified nano-silica composite material #1.

[0031] Modified Nano-Silica Composite Material #2

[0032] S1: Preparation of borate monomer: 22.39 g (0.103 mol) of 2,2'-(octylimino)diethanol, 14.6 g (0.1 mol) of triethyl borate and 200 ml of solvent toluene were placed in a reaction vessel equipped with an oil-water separator (containing 10 g of zinc chloride) and a vacuum pressure reducing device, the water bath was controlled at 65°C, the vacuum degree was controlled at 0.03 MPa, the mixture was refluxed under reduced pressure, and the reaction was stirred for 1.5 h; 11.11 g (0.11 mol) of N-hydroxymethyl acrylamide and 0.011 g of inhibitor phenothiazine were added, the reaction was continued for 1.5 h, and the unreacted raw materials and solvent were removed by vacuum distillation to obtain a borate monomer;

[0033] S2: Add 15g protective colloid gelatin, 10g emulsifier Tween T-40, and 100ml deionized water into another reaction container, stir for 4min, then add 93g nano-silica, stir under ultrasonication, heat to 80°C, add 2g methyl methacrylate and 0.03g initiator tert-butyl hydroperoxide, and react for 4.5h;

[0034] S3: 5 g of borate monomer was added dropwise to the reaction system obtained in S2, and then 0.05 g of initiator tert-butyl hydroperoxide was added thereto, the temperature was raised to 85°C, and after reacting for 11 hours, a demulsifier - a 5% by mass aluminum sulfate aqueous solution was added, the demulsifier was demulsified, filtered, washed, and vacuum dried to obtain the modified nano-silica composite material #2.

[0035] Modified Nano-Silica Composite Material #3

[0036] S1: Preparation of borate monomer: 19.66 g (0.105 mol) of 2,2'-(cyclohexylimino)diethanol, 14.6 g (0.1 mol) of triethyl borate and 200 ml of solvent toluene were placed in a reaction vessel equipped with an oil-water separator (containing 10 g of copper sulfate) and a vacuum pressure reducing device, the water bath was controlled at 70°C, the vacuum degree was controlled at 0.02 MPa, the mixture was refluxed under reduced pressure, and the reaction was stirred for 1 hour; 12.12 g (0.12 mol) of N-hydroxymethyl acrylamide and 0.024 g of inhibitor phenothiazine were added, the reaction was continued for 1 hour, and the unreacted raw materials and solvent were removed by vacuum distillation to obtain a borate monomer;

[0037] S2: Add 20g of protective colloid sodium carboxymethyl cellulose, 15g of emulsifier Tween T-40, and 100ml of deionized water into another reaction container, stir for 5min, then add 95g of nano-silica, stir under ultrasonication, heat to 90°C, add 2g of methyl methacrylate and 0.04g of initiator tert-butyl hydroperoxide, and react for 5h;

[0038] S3: 3 g of borate monomer was added dropwise to the reaction system obtained in S2, and then 0.06 g of initiator tert-butyl hydroperoxide was added thereto, the temperature was raised to 90°C, and after reacting for 10 hours, a demulsifier - a 5% by mass aluminum sulfate aqueous solution was added, the demulsifier was demulsified, filtered, washed, and vacuum dried to obtain the modified nano-silica composite material #3.

[0039] Modified Nano-Silica Composite Material #4

[0040] The same as modified nano-silica composite material #1, except that the mass of the borate monomer used is 8 g.

[0041] Example 1

[0042] 8 parts of tannic acid are dissolved in 100 parts of deionized water to form a tannic acid aqueous solution, which is then mixed with 100 parts of polyacrylic acid and 10 parts of modified nano-silicon dioxide composite material #1 and mechanically dispersed until uniform, thereby obtaining the self-healing modified binder for lithium battery silicon negative electrode.

[0043] Example 2

[0044] 15 parts of tannic acid are dissolved in 100 parts of deionized water to form a tannic acid aqueous solution, which is then mixed with 125 parts of polyacrylic acid and 12 parts of modified nano-silicon dioxide composite material #2 and mechanically dispersed until uniform, thereby obtaining the self-healing modified binder for lithium battery silicon negative electrode.

[0045] Example 3

[0046] 25 parts of tannic acid are dissolved in 100 parts of deionized water to form a tannic acid aqueous solution, which is then mixed with 150 parts of polyacrylic acid and 15 parts of modified nano-silicon dioxide composite material #3 and mechanically dispersed until uniform, thereby obtaining the self-healing modified binder for lithium battery silicon negative electrode.

[0047] Example 4

[0048] Same as Example 1, except that the modified nano-silicon dioxide composite material #1 is replaced by a modified nano-silicon dioxide composite material #4.

[0049] Comparative Example 1

[0050] Same as Example 1, except that tannic acid is not added.

[0051] Comparative Example 2

[0052] Same as Example 1, except that the modified nano-silicon dioxide composite material #1 is not added.

[0053] Comparative Example 3

[0054] Same as Example 3, except that the amount of modified nano-silicon dioxide composite material #3 used is 17 parts.

[0055] Performance Testing

[0056] 80 mg of silicon active material (nano silicon powder) and 20 mg of conductive agent (acetylene black) were placed in a mortar and ground thoroughly for 20 minutes, and then 150 mg of the modified binder obtained in Examples 1-4 and Comparative Examples 1-3 were added, and the grinding was continued until mixed to obtain a paste slurry with suitable viscosity; the electrode slurry was evenly and evenly coated on the copper foil with an infrared drying flat coater, and naturally air-dried at room temperature for 24 hours, and then vacuum-dried at 60°C for 10 hours; the dried electrode sheet was rolled by a double-roller machine, and then cut into pieces with a slicer to obtain a circular electrode sheet with a radius of 8 mm, and dried at 110°C for 12 hours under vacuum conditions to obtain a silicon negative electrode sheet.

[0057] The silicon negative electrode sheet and lithium sheet prepared above were used as the negative electrode and positive electrode of the lithium-ion battery respectively, Celgard 2400 single-layer polypropylene film was used as the separator, and a mixed solution of 1 mol / L LiPF6 ethylene carbonate (EC) and diethyl carbonate (EMC) (v / v=1:1) was used as the electrolyte solution. The CR2032 button cell was assembled in a glove box filled with argon gas to obtain a lithium-ion battery. (This preparation process is only used as an example and is not limited to any conditions)

[0058] Peel strength: Use an electronic universal testing machine (DL-D model) to perform a 180° peeling test on the pole piece to test the bonding strength of the pole piece;

[0059] Healing ability: Use a knife to make several cuts on the surface of the silicon negative electrode, leave it at room temperature for a certain period of time, observe the surface recovery, and record the healing time;

[0060] Electrochemical performance: The above lithium-ion battery was subjected to constant current charge and discharge test at room temperature. Specifically, the button cell was charged and discharged at a constant current of 0.5C within a voltage range of (3-0.01) V to test its first discharge capacity, first coulomb efficiency and capacity retention after 100 cycles.

[0061] The test results are shown in Table 1:

[0062] Table 1 Performance test results of modified adhesives obtained in Examples 1-4 and Comparative Examples 1-3

[0063]

[0064] From the data in Table 1, it can be seen that the modified binder provided by the present invention has excellent self-healing properties, and the prepared negative electrode plate can recover the gap within 8s, which provides a powerful condition for optimizing the battery cycle performance: From the battery charge and discharge cycle test, it can be seen that the silicon negative electrode plate has good cycle performance and excellent comprehensive performance; and it also has a resistance of not less than 0.6 N·cm -1 The average peel strength.

[0065] The results of Example 4 show that when preparing the modified nano-silica composite material, the quality of the borate monomer used is not necessarily better. When it exceeds a certain range, the peel strength and self-healing properties of the obtained electrode are weakened to a certain extent, and the capacity retention rate after cycling is reduced. This may be because during the operation of the electrode, a viscous polymer will appear inside, affecting its cyclic charge and discharge performance.

[0066] The results of Comparative Example 3 show that the more the modified nano-silicon dioxide composite material is added, the better it is. Excessive addition may also lead to an increase in the polarity of the molecules inside the electrode, affecting the charge and discharge performance of the battery.

Claims

1. A self-healing modified binder for lithium battery silicon negative electrode, characterized in that: The raw materials for preparation include at least 100-150 parts of polyacrylic acid, 8-25 parts of tannic acid and 10-15 parts of modified nano-silicon dioxide composite material; wherein the modified nano-silicon dioxide composite material is prepared by copolymerization of borate monomer and methyl methacrylate on the surface of nano-silicon dioxide; The preparation method of the modified nano-silicon dioxide composite material comprises the following steps: S1: Preparation of borate monomer: N,N-dihydroxyethyl alkylamine, triethyl borate and solvent are placed in a reaction vessel equipped with an oil-water separator and a vacuum pressure reducing device, the water bath is controlled at 60-70°C, the vacuum degree is controlled at 0.02-0.04MPa, the reaction is carried out under reduced pressure and refluxed, and the reaction is stirred for 1-2h; N-hydroxymethyl acrylamide and a polymerization inhibitor are added, the reaction is continued for 1.5-2h, and unreacted raw materials and solvent are removed by reduced pressure distillation to obtain a borate monomer; S2: Add protective colloid, emulsifier and deionized water into another reaction container, stir for 3-5 minutes, then add nano-silicon dioxide slurry, stir under ultrasonic wave, heat to 70-90°C, add methyl methacrylate and initiator, and react for 4-5 hours; S3: Add borate monomer to the reaction system obtained in S2, then add initiator, heat to 80-90°C, react for 10-12h, add demulsifier, demulsify, filter, wash, and vacuum dry to obtain the modified nano-silica composite material.

2. The self-healing modified binder for lithium battery silicon negative electrode according to claim 1, characterized in that: The N,N-dihydroxyethylalkylamine described in S1 is at least one of N-butyldiethanolamine, N-heptyldiethanolamine, 2,2'-(octylimino)diethanol, 2,2'-(cyclohexylimino)diethanol, p-ethyldihydroxyethylcyclohexylamine, and N,N-dihydroxyethyldodecylamine.

3. The self-healing modified binder for lithium battery silicon negative electrode according to claim 1, characterized in that: The molar ratio of N,N-dihydroxyethyl alkylamine to triethyl borate and N-hydroxymethyl acrylamide in S1 is 1-1.05:1:1-1.

2.

4. The self-healing modified binder for lithium battery silicon negative electrode according to claim 1, characterized in that: The solvent in S1 is at least one of benzene, toluene, pentane, hexane, ether and acetone.

5. The self-healing modified binder for lithium battery silicon negative electrode according to claim 1, characterized in that: The oil-water separator in S1 is filled with at least one of magnesium chloride, calcium chloride, zinc chloride and copper sulfate for absorbing the generated ethanol.

6. The self-healing modified binder for lithium battery silicon negative electrode according to claim 1, characterized in that: The initiator described in S2 is at least one of persulfates and peroxides, and its usage accounts for 1-2% of the mass of methyl methacrylate; the initiator described in S3 is at least one of persulfates and peroxides, and its usage accounts for 1-2% of the mass of borate monomer.

7. The self-healing modified binder for lithium battery silicon negative electrode according to claim 1, characterized in that: The nano-silica contained in the nano-silica slurry used in S2 satisfies the mass ratio of methyl methacrylate: borate monomer: nano-silica = 1-5: 3-7: 90-95 in the system.

8. The method for preparing the self-healing modified binder for lithium battery silicon negative electrode according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: dissolving tannic acid in deionized water to form a tannic acid aqueous solution, then mixing the tannic acid aqueous solution with polyacrylic acid and a modified nano silicon dioxide composite material, and mechanically dispersing the mixture until uniform, thereby obtaining the self-healing modified binder for the lithium battery silicon negative electrode.

9. Use of the self-healing modified binder for lithium battery silicon negative electrode according to any one of claims 1 to 7 in lithium battery silicon negative electrode pole pieces.

Citation Information

Patent Citations

  • Low-temperature-resistant lithium ion battery containing activated carbon negative electrode material and preparation method of low-temperature-resistant lithium ion battery

    CN117317188A

  • Curable and Solvent Soluble Formulations and Methods of Making and Using Therof

    US20200062877A1